2013
DOI: 10.1007/s11250-013-0524-y
|View full text |Cite
|
Sign up to set email alerts
|

Genetic association between milk yield, stayability, and mastitis in Holstein cows under tropical conditions

Abstract: The objective of this study was to estimate genetic parameters for milk yield, stayability, and the occurrence of clinical mastitis in Holstein cows, as well as studying the genetic relationship between them, in order to provide subsidies for the genetic evaluation of these traits. Records from 5,090 Holstein cows with calving varying from 1991 to 2010, were used in the analysis. Two standard multivariate analyses were carried out, one containing the trait of accumulated 305-day milk yields in the first lactat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
2
2
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 27 publications
4
2
2
4
Order By: Relevance
“…Sasaki (2013) reviewed the genetic parameters for longevity traits of dairy cattle and stated that the variations among estimates of most of the estimates of heritability obtained by the linear model are <0.10. Our estimates were lower than those reported by Pfeiffer et al (2015) in Austrian Fleckvieh cattle and Irano et al (2014) in Holstein cows under tropical conditions.…”
Section: Resultscontrasting
confidence: 94%
“…Sasaki (2013) reviewed the genetic parameters for longevity traits of dairy cattle and stated that the variations among estimates of most of the estimates of heritability obtained by the linear model are <0.10. Our estimates were lower than those reported by Pfeiffer et al (2015) in Austrian Fleckvieh cattle and Irano et al (2014) in Holstein cows under tropical conditions.…”
Section: Resultscontrasting
confidence: 94%
“…Vallimont, Dechow, Sattler and Clay (2009) and Wolf et al (2010) reported genetic correlation between milk yield and NumMast case as 0.25 and 0.34, respectively. However, Irano et al (2014) reported a negative genetic correlation between cumulative 305-day milk yield and Mast in Holstein cows in tropical condition of Brazil. Genetic correlation between Firstmilk and measures of mastitis was relatively similar to those of Milk305 and measures of mastitis.…”
Section: Resultsmentioning
confidence: 94%
“…2 ) foi maior do que a variância genética aditiva (860,53kg A estimativa de herdabilidade para a PR305 foi de 0,16 (Tabela 2), valor que se encontra abaixo dos relatados por outros estudos com a raça Holandesa no Brasil, variando entre 0,19 a 0,30 (ANDRADE et al, 2007;IRANO et al, 2014). A magnitude da estimativa de herdabilidade para a produção de leite obtida neste trabalho indica que, apesar da baixa magnitude, é possível obter ganhos via seleção.…”
Section: Ciência Rural V45 N12 Dez 2015unclassified
“…Na literatura, estimativas de herdabilidade para a MC têm sido menores do que os valores relatados Tabela 1 -Número de animais (n), médias, desvios padrão (DP) e coeficientes de variação (CV%) para a produção de leite acumulada, até 305 dias (PR305), e ocorrência de mastite clínica (MC). IRANO et al (2014), no Brasil, que relataram estimativas entre 0,08 a 0,13. A estimativa de repetibilidade para a PR305 foi de 0,34±0,012 e para a MC foi de 0,21±0,02 (Tabela 2).…”
Section: Ciência Rural V45 N12 Dez 2015unclassified
See 1 more Smart Citation